Improving Students' Vocabulary Mastery Through Digital Storytelling Technique at XI MIA2 Class of SMA Negeri 7 Tual - Ferdinandus, Marcy Saartje; Tharob, Theresia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to improve the mastery of English vocabulary of grade XI MIA2 students at SMA Negeri 7 Tual through digital storytelling techniques. The type of research used is Classroom Action Research (CAR) research which is carried out in two cycles to determine the significant improvement in students' vocabulary mastery after the application of this method. Data collection techniques use tests, questionnaires, observations, documentation. Data analysis was carried out descriptively on all research data. The results of the data analysis showed that the proportion of students who met the minimum completeness criteria increased significantly from the first cycle to the second cycle. The positive response of students to the use of Digital Storytelling in English learning also confirms this finding. Thus, it can be concluded that the Digital Storytelling technique is an effective approach in improving vocabulary mastery and providing a more engaging and interactive learning experience for students